Reflective thinking processes as a tool for social justice - Fumiatti, S.S. (International Journal of Pedagogy and Curriculum, 2025)
In the United States (US) kindergarten through twelfth-grade public school system, the classroom library has come to be a critical part of literacy instruction within the language arts classroom. This fact is especially true in the middle school grade levels (grades five through eight), where reading volume begins to rapidly increase. Additionally, a developmental norm for students within this age range includes a growing sense of independence and choice, as well as a desire to share and voice opinions. Classroom libraries have come to be tools that are used regularly and are heavily influential on the way that students grow to perceive themselves, the world around them, and the way they fit into that world. However, classroom libraries have remained stagnant and underrepresent the diverse populations of the students in those classrooms. This article aims to connect deep reflective thinking with anti-oppressive and transformative learning theories, exploring how these frameworks can be used to problematize current practices in classroom libraries. Through a content analysis of what is seen as deep and critical thinking practices and reflective thinking practices, anti-oppressive and transformative learning theories can be linked to foster a social justice classroom culture within US public middle school language arts classrooms. © 2025 Common Ground Research Networks. All rights reserved.
Keywords: Anti-oppressive Education; Classroom Libraries; Reflective Thinking; Social Justice; dept.edu; peer-reviewed